Gut metagenomic features of frailty - Jarmukhanov, Zharkyn; Mukhanbetzhanov, Nurislam; Vinogradova, Elizaveta; Kozhakhmetov, Samat; Kushugulova, Almagul (Frontiers in Cellular and Infection Microbiology, 2024)
This study investigates the relationship between frailty severity and gut microbiome characteristics in adults in Kazakhstan. We analyzed 158 participants across four frailty severity (mild to very severe) using metagenomic sequencing of stool samples. Frailty was significantly correlated with age, weight, and functional measures like walking speed and grip strength. Microbial diversity decreased significantly with increasing frailty. Beta diversity analysis revealed distinct clustering patterns based at phylum level. Taxonomically, we observed a significant inverse correlation between Firmicutes abundance and frailty. Classes like Clostridia and Erysipelotrichia decreased with frailty, while Bacteroidia and Actinobacteria increased. At the family level, Oscillospiraceae showed a positive correlation with frailty. Functionally, we identified significant correlations between frailty measures and specific metabolic pathways. The frailty index negatively correlated with pathways involved in cobalamin, arginine and molybdenum cofactor biosynthesis and positively correlated with folate biosynthesis. Physical performance measures strongly correlated with pathways related to nucleotide biosynthesis, and one-carbon metabolism. We propose these identified features may constitute a “frailty-associated metabolic signature” in the gut microbiome. This signature suggests multiple interconnected mechanisms through which the microbiome may influence frailty development, including modulation of inflammation, alterations in energy metabolism, and potential impacts on muscle function through microbial metabolites.